The Scale of Agricultural Production–Some Corrections - Hopkins, J. A. (Quarterly Journal of Economics, 1940)
Journal Article The Scale of Agricultural Production — Some Corrections Get access J. A. Hopkins J. A. Hopkins WPA National Research Project Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 54, Issue 2, February 1940, Pages 314–316, https://doi.org/10.2307/1883338 Published: 01 February 1940